DESIGN OF AUTOMATIC SLIDING DOOR BASED ON ARDUINO USING ULTRASONIC SENSORS AS A PREVENTATIVE THE SPREAD OF COVID-19 - Sidik Susilo; Erny Listijorini; Fikri Ardiansyah; Ula, Shofiatul Ula (DINAMIS, 2023)
Covid-19 is an infectious disease caused by acute respiratory syndrome coronavirus 2 (Sars-CoV-2), therefore a study is conducted to break the chain the spread of the coronavirus is a touchless automatic door. In this study, an automatic door is made, and this door uses an Arduino-based ultrasonic sensor. This research aims to be able to design and build sliding doors for automatic doors and can create an Arduino system that is suitable for automatic doors and can use ultrasonic sensors as a touchless medium. This research uses tools and materials, namely Arduino Uno, ultrasonic sensor, dc motor, l298n motor driver, and for the driving mechanism is a dc motor connected to the pinion sprocket and a chain connected to the door surface. This research designs doors in SolidWorks 2018 software and builds doors with specifications (Material: PVC, Height: 1900 mm, Width: 610 mm, Thickness: 40 mm, Mass: 7.5 kg, Weight: 73.5 N) in a street workshop in Leuweung Sawo Cilegon-Banten, as well as making an Arduino system for doors that can move automatically by making a coding program in the Arduino IDE software, for opening and closing the door with an ultrasonic sensor that is set at a distance of about 5 cm..